Prevalence and Related Factors of Anxiety Among University Teachers 1 Year After the COVID-19 Pandemic Outbreak in China: A Multicenter Study - Fu, Wenning; Han, Xiaotong; Liu, Yifang; Zou, Li; Wen, Jing; Yan, Shijiao; Lv, Chuanzhu (Frontiers in Psychiatry, 2022)
Objectives: This study aimed to evaluate the prevalence of anxiety among university teachers one year after the onset of the coronavirus disease 2019 (COVID-19) pandemic and provide empirical evidence of psychological intervention. Methods: A multicenter study was conducted to examine the prevalence of anxiety among 10,302 teachers in 21 Chinese universities from February 12 to April 23, 2021. The generalized Anxiety Disorder 7-item Scale (GAD-7) was used to assess symptoms of anxiety. Multivariate logistic regression models were used to analyze the relationship between potential influence and anxiety symptoms. Results: The overall prevalence of anxiety was 40.0% one year after the onset of the COVID-19 pandemic, which was found to be higher in women than in men (41.32% vs. 38.22%; p <0.0001). The multivariate logistic regression showed that being the female (OR=1.207; 95%CI:1.103-1.318), age ≥60 years (OR=2.004; 95%CI:1.128-3.560), being married (OR=1.319; 95%CI:1.150-1.513), and poor family economic status (OR=1.580; 95%CI:1.321-1.891) were significantly associated with anxiety. Participants with moderate, slight, or no impact of COVID-19 on life (OR for moderate, 0.557; 95%CI, 0.508-0.611; OR for slight/no, 0.377; 95%CI, 0.323-0.439) showed a reduced risk of anxiety compared to those who reported a significant effect. Conclusions: Symptoms of anxiety were found in about two-fifths of Chinese university teachers one year after the outbreak of the COVID-19 pandemic. Our findings suggest that the government should improve the dynamic tracking of mental health and adopt long-term intervention strategies.